Manufacturing method of conductive fiber
By immersion and ball milling machine treatment by dispersing SWCNT inks scattered SWCNT in the intangible subwelling solvent, and combined with the vacuum drying method, the problem of not firmly attached the SWCNT conductive film on the synthetic fiber, realizing the high conductivity and the strong interface densely intertwined properties Essence
Patent Information
- Application Number
- CN202411003902.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-25
- Filing Date
- 2024-07-25
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, when the SWCNT conductive film is formed on synthetic fibers, adhesive and surfactant are easily retained, resulting in a decrease in conductivity. In the polyester fiber with high crystallinity, the interface bonding strength is weak, resulting in SWCNT. The characteristics of the product cannot be fully utilized.
The conductive ink with single -layer carbon nanotubes scattered in an intangible sub -solvent is impregnated with a single -layer carbon nanotuba, combined with ball mill treatment and vacuum drying method to ensure that the conductive membrane is firmly attached to the synthetic fiber, and the solvent is removed to improve the interface density.
The solid attachment of the SWCNT conductive film on the synthetic fiber is achieved, the conductivity and interface tightness strength is improved, the residues of the adhesive and surfactant are avoided, and the characteristics of the SWCNT are fully utilized.
Smart Images

Figure CN119372914A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for producing conductive fibers. Background Art
[0002] Single-wall carbon nanotubes (SWCNTs) have excellent mechanical, electrical, and thermal properties and are highly flexible, so, for example, SWCNT films containing SWCNTs are expected to be used as next-generation flexible conductive materials.
[0003] Various studies have been conducted to laminate a SWCNT conductive film on the surface of synthetic fibers to impart a function as conductive fabric. JP2010-059561A discloses a technique for forming a SWCNT conductive film on synthetic fibers using a dispersion containing SWCNTs, a binder, and a surfactant as a dispersant for SWCNTs. Summary of the invention
[0004] However, in JP 2010-059561 A, the formed SWCNT conductive film still contains a binder component and a surfactant component added as a dispersant. Since these components are non-conductive, it is believed that the electrical properties such as the conductivity of the SWCNT conductive film are reduced. In addition, for polyester fibers (PET fibers) with high crystallinity and stable surface properties, there are problems such as weak interfacial adhesion, peeling, and inability to fully utilize the properties of SWCNT.
[0005] The present invention has been made in view of the problems of the prior art. An object of the present invention is to provide a method for producing conductive fibers in which a carbon nanotube conductive film is firmly attached to a synthetic fiber.
[0006] The method for manufacturing a conductive fiber of the present embodiment is a method for manufacturing a conductive fiber comprising a synthetic fiber and a conductive film comprising a single-layer carbon nanotube formed on the surface of the synthetic fiber, and comprises: a conductive ink impregnation step, in which the conductive ink in which the single-layer carbon nanotube is dispersed in an aprotic solvent is impregnated into the synthetic fiber to make it adhere; and a solvent removal step, in which, after the conductive ink impregnation step, the synthetic fiber to which the conductive ink is adhered is dried to remove the aprotic solvent.
[0007] According to the present invention, it is possible to provide a method for producing conductive fibers in which a carbon nanotube conductive film is firmly attached to a synthetic fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 This is a cross-sectional view schematically showing the conductive fiber according to the present embodiment.
[0009] Figure 2This is an enlarged view schematically showing a state where an aprotic solvent has permeated into the synthetic fiber of the present embodiment.
[0010] Figure 3 This is a schematic diagram showing a method for producing the conductive fiber according to the present embodiment.
[0011] Figure 4A This is a SEM photograph of the magnified surface state of the synthetic fiber (PET fiber).
[0012] Figure 4B is magnified by Figure 4A SEM photograph of the surface state of the conductive fiber made of synthetic fiber.
[0013] Figure 5A This is a SEM photograph of the magnified surface state of the synthetic fiber (PET fiber).
[0014] Figure 5B is magnified by Figure 5A SEM photograph of the surface state of the conductive fiber made of synthetic fiber.
[0015] Fig. 6A This is an optical image showing the conductive fiber of this embodiment.
[0016] Figure 6B This is an optical image showing a conductive fiber having a conductive film on the surface of the circular cross-section fiber.
[0017] Figure 7 This is a schematic diagram of the experiment for measuring sheet resistance.
[0018] Figure 8 This is a schematic diagram of an experiment to measure electromagnetic wave shielding properties. DETAILED DESCRIPTION
[0019] Hereinafter, the method for producing the conductive fiber according to the present embodiment will be described in detail using the drawings. It should be noted that the dimensional ratios in the drawings are exaggerated for the sake of convenience of description and may be different from the actual ratios.
[0020] [Conductive fiber]
[0021] Figure 1 The conductive fiber 1 shown includes a synthetic fiber 10 and a conductive film 20 including a single-walled carbon nanotube (hereinafter referred to as SWCNT) 25 formed on the surface of the synthetic fiber 10. The conductive ink 24 in which the SWCNT 25 is dispersed in an aprotic solvent 23 is impregnated in the synthetic fiber 10 to adhere to the conductive film 20, thereby forming the conductive fiber 1 in which the conductive film 20 is firmly attached to the synthetic fiber 10.
[0022] (synthetic fiber)
[0023] The synthetic fiber 10 is not particularly limited, but is preferably at least one selected from the group consisting of polyester fibers, polyamide (nylon) fibers, polyolefin fibers, acrylic fibers, polyurethane fibers, and cellulose fibers. Among them, for polyethylene terephthalate fibers (hereinafter referred to as PET fibers), which are one type of polyester fibers, the conductive ink 24 in which SWCNT 25 is dispersed in the aprotic solvent 23 is easily permeated, and the conductive film 20 is easily firmly attached. Therefore, as the synthetic fiber 10, polyester fibers are more preferred, and PET fibers are further preferred. The structure of PET fibers is shown in Chemical Formula 1.
[0024] [Chemistry 1]
[0025]
[0026] (Conductive film)
[0027] The conductive film 20 includes SWCNT. The central diameter of the SWCNT 25 included in the conductive film 20 is, for example, 0.5 nm to 5 nm, and preferably 1 nm to 3 nm from the viewpoint of conductivity. In addition, the length of the SWCNT 25 included in the conductive film 20 is, for example, 1 μm to several tens of μm. Furthermore, the thickness of the conductive film 20 is, for example, 50 nm to 500 nm, and preferably 100 nm to 200 nm from the viewpoint of adhesion of the interface with the synthetic fiber 10.
[0028] The conductive ink 24 in which SWCNTs 25 are dispersed in the aprotic solvent 23 is impregnated on the synthetic fiber 10 to adhere to the conductive ink, and the synthetic fiber 10 is dried to remove the aprotic solvent 23 , so that the conductive film 20 including SWCNTs is firmly attached to the surface of the synthetic fiber 10 .
[0029] The conductive fiber 1 is produced by the conductive fiber production method described below.
[0030] [Method for producing conductive fiber]
[0031] The method for producing a conductive fiber is a method for producing a conductive fiber 1 including a synthetic fiber 10 and a conductive film 20 including SWCNTs 25 formed on the surface of the synthetic fiber 10. The method for producing the conductive fiber 1 includes a conductive ink impregnation step and a solvent removal step.
[0032] (Conductive ink impregnation process)
[0033] like Figure 3 As shown, the conductive ink impregnation step is a step of impregnating the conductive ink 24 in which the SWCNTs 25 are dispersed in the aprotic solvent 23 into the synthetic fiber 10 to make it adhere.
[0034] A non-protonic solvent 23 is used as a dispersing solvent for the conductive ink 24. As the non-protonic solvent 23, at least one selected from the group consisting of DMF (N,N-dimethylformamide), DMSO (dimethyl sulfoxide), DMA (N-methylacetamide), and acetonitrile is preferred. Both the non-protonic solvent 23 and the SWCNT 25 have high polarity, and even without adding a dispersant such as a surfactant, the SWCNT 25 is uniformly dispersed in the non-protonic solvent 23, and a good conductive ink of the SWCNT 25 alone is obtained. In the case where the synthetic fiber 10 is a PET fiber, DMF is more preferred from the viewpoint of being easy to penetrate into the inside of the PET fiber.
[0035] DMF is an amide formed by the condensation of formic acid and dimethylamine. Amide bonds are relatively stable bonds and are difficult to react with nucleophiles and electrophiles, so they are used as organic solvents. Because they have carbonyl groups, they are polarized and have high polarity, so they are called aprotic polar solvents. On the other hand, SWCNT25 shows the characteristics of high polarity, high stereoregularity, and molecules that easily attract and aggregate with each other. Since DMF molecules have amide bonds, amide bonds and carbon are easily adsorbed, so even without adding dispersants such as surfactants, conductive ink 24 in which SWCNT25 is uniformly dispersed in DMF solvent can be obtained.
[0036] The solubility parameter (SP value) of DMF is 12.0, which is similar to the solubility parameter 10.7 of PET fiber. Therefore, DMF is easy to penetrate into the non-crystalline part inside the surface-stable crystalline polymer such as PET fiber, causing swelling and softening on the surface of PET fiber, and the surface of PET fiber is modified. The change of the surface state of PET fiber caused by this DMF has a great influence on the adhesion of the interface.
[0037] The SP value is an indicator of the magnitude of the intermolecular force (cohesion energy density) of a substance, expressed in 1 cm 3 The square root of the heat of evaporation required to evaporate a liquid. Substances with similar SP values (σ) are more likely to mix with each other and have greater solubility. SP value ((cal / cm 3 ) 1 / 2 ) can be calculated by the following mathematical formula (1).
[0038] SP=((ΔH-RT) / V) 1 / 2 =(d / M·(CE)) 1 / 2 (1)
[0039] In the above mathematical formula (1), the latent heat of vaporization ΔH (cal / mol), the gas constant R (cal / mol), the absolute temperature T (K), the molar volume V (cm 3 / mol), density d(g / cm 3), gram molecular weight (g / mol), and cohesive energy CE (cal / mol).
[0040] like Figure 2 As shown, the crystalline part 11 and the amorphous part 12 of the synthetic fiber 10 (PET fiber) form a microphase separation structure. When the non-protonic solvent 23 (DMF) acts here, DMF invades the amorphous part 12 of the PET fiber, causing softening and swelling. This action becomes more active when the temperature rises, and the activity of the molecules becomes more active, so that they penetrate deeper into the inside. The glass transition temperature of PET fiber is 70°C, so if it reaches above 70°C, the activity of the molecules in the crystalline part 11 also becomes active, and DMF also penetrates into the inside of the crystalline part 11, causing the crystal structure to collapse. During recrystallization, the dispersion of the crystal grains becomes unstable, which may cause a decrease in physical properties. Therefore, in order to maintain the physical properties of PET fiber, the action of DMF needs to be carried out at a temperature below 70°C.
[0041] In addition, the interface between PET fiber and SWCNT is entangled with each other in the surface layer due to the softening and swelling of PET fiber. Moreover, when DMF is removed, PET fiber returns to its original state, which can improve the adhesion strength of the interface, thus forming a strong conductive film of SWCNT alone.
[0042] As described above, the conductive ink 24 does not need to contain a dispersant and may not contain a surfactant. As in the past, if a surfactant component added as a dispersant remains in the conductive film, the electrical properties such as the conductivity of the conductive film are considered to be reduced because the surfactant component is non-conductive. Therefore, by not containing a surfactant in the conductive ink 24, it is possible to produce a conductive fiber 1 having higher electrical properties than before.
[0043] The method for preparing the conductive ink 24 in which the SWCNT 25 is dispersed in the aprotic solvent 23 is not particularly limited. In order to make the dispersibility of the SWCNT 25 in the aprotic solvent 23 good, for example, a pulverizer such as a ball mill, a rotor high-speed mill, a cutting mill, a homogenizer, a vibration mill, and a grinder can be used to grind and disperse it in the aprotic solvent 23. Both the aprotic solvent 23 and the SWCNT 25 have high polarity, and the SWCNT 25 can be uniformly dispersed in the aprotic solvent 23 even without adding a dispersant such as a surfactant. In addition, in the aprotic solvent 23, the wettability of the SWCNT 25 is improved, and the SWCNT 25 can be finely disentangled.
[0044] The method of impregnating the conductive ink 24 into the synthetic fiber 10 to attach the conductive ink 24 is not particularly limited, and a general impregnation treatment method such as a method of applying microvibration for treatment can be used. However, it is believed that when microvibration is applied, the temperature of the conductive ink 24 rises, and the aprotic solvent 23 becomes easy to penetrate into the inside of the synthetic fiber 10, and the corrosiveness to the synthetic fiber 10 becomes stronger, causing the dissolution of the synthetic fiber 10, the change of the crystal structure, and the deterioration of the physical properties.
[0045] Therefore, as a method of impregnating the conductive ink 24 into the synthetic fiber 10 to make it adhere, Figure 3 As shown, it is preferable to use a ball mill 50. In order to form a uniform conductive film 20 on the synthetic fiber 10 in a form that maintains the dispersibility of the SWCNT 25 in the aprotic solvent 23, the synthetic fiber 10 and the conductive ink 24 are put into the ball mill 50, and the conductive ink 24 is dispersed on the synthetic fiber 10 while stirring. A certain amount of balls 51 as a dispersion medium are put into the cylindrical container of the ball mill 50. And, if the ball mill 50 is rotated with the horizontal axis as the center, the balls 51 are lifted to a certain height along the inner wall along with the rotation of the cylindrical container, slide or roll on the inner wall, and circulate in a certain direction in the cylindrical container. During the circulation of the balls 51, a uniform conductive film 20 can be formed on the synthetic fiber 10. The method using such a ball mill 50 has almost no temperature rise, can suppress the aprotic solvent 23 from penetrating into the inside of the synthetic fiber 10, can suppress the reduction of the physical properties of the synthetic fiber 10, and at the same time, the conductive film 20 is laminated on the synthetic fiber 10.
[0046] The concentration of SWCNT 25 in conductive ink 24 is preferably 0.01 to 0.5 mass%, more preferably 0.05 to 0.2 mass%, and further preferably 0.08 to 0.12 mass%, based on 100 mass% of conductive ink 24. When the concentration of SWCNT 25 is within the above range, uniform conductive film 20 can be easily formed.
[0047] Before the conductive ink impregnation process, there may be a pre-treatment process of impregnating the synthetic fiber in polydopamine (hereinafter referred to as PDA). PDA is a substance that imitates the protein of the byssus of the blue mussel (a kind of bivalve), and is a catechol-based polymer that has a catechol group, an amino group, a benzene ring, and is combined with various materials. It can change the surface properties of hydrophilic cotton fibers, hydrophobic PET fibers, etc., and improve the adhesion with the conductive film containing SWCNT. PDA is a polymer formed by self-polymerization of dopamine while oxidizing it in an oxygen atmosphere and under alkaline conditions. The dopamine shown on the left side of Chemical Formula 3 becomes the PDA shown on the right side through an intermediate.
[0048] By implementing a pretreatment step of immersing in PDA, the surface of hydrophilic or hydrophobic fibers can be modified through interactions with dopamine derivatives (hydrogen bonds, π-π interactions, etc.). In particular, cotton fibers, which are a type of cellulose fibers having hydroxyl groups as shown in Chemical Formula 2, have high water absorption, so it is preferred to implement a pretreatment step of immersing in PDA. By pretreatment with PDA, the hydroxyl groups of the cotton fibers are hydrogen-bonded to each other, and the surface can be modified to be hydrophobic, which can improve the adhesion with the hydrophobic SWCNT.
[0049] [Chemistry 2]
[0050]
[0051] [Chemistry 3]
[0052]
[0053] When the pretreatment step of immersing the PET fibers in PDA is performed, the PET fibers have a certain degree of water absorption, and thus π-π interactions are exerted between the PET fibers and the benzene rings present in dopamine, thereby increasing the hydrophobicity and improving the adhesion of the interface.
[0054] (Solvent Removal Process)
[0055] The solvent removal step is a solvent removal step in which the synthetic fiber 10 to which the conductive ink 24 is attached is dried to remove the aprotic solvent 23 after the conductive ink impregnation step. As described above, when the synthetic fiber 10 reaches a temperature higher than the glass transition temperature, the activity of the molecules in the crystal part becomes active, the solvent also penetrates into the crystal, the crystal structure collapses, and the dispersion of the crystal grains becomes unstable during recrystallization, which may cause a decrease in physical properties. Therefore, the temperature of the solvent removal step is preferably lower than the glass transition temperature of the synthetic fiber 10.
[0056] From the perspective of the adhesion of the conductive film 20 to the synthetic fiber 10, the solvent removal process preferably uses a vacuum drying method. For example, when DMF is used as the aprotic solvent 23 and PET fiber is used as the synthetic fiber 10, the boiling point of DMF is 153°C, so in order to remove DMF from the PET fiber, a drying condition of more than 150°C is required. However, if the PET fiber is heated to a glass transition temperature of 70°C or more, DMF invades the crystal structure of the PET fiber, and the physical properties of the PET fiber are reduced. Therefore, it is preferred to use vacuum drying to remove the solvent at a temperature below 70°C. Moreover, during drying, the PET fiber swollen by DMF shrinks to its original state, and in this process, the adhesion of the interface can be made stronger.
[0057] As described above, the method for producing the conductive fiber 1 of the present embodiment is a method for producing the conductive fiber 1 including the synthetic fiber 10 and the conductive film 20 containing SWCNT 25 formed on the surface of the synthetic fiber 10. The method for producing the conductive fiber 1 includes a conductive ink impregnation step of impregnating the conductive ink 24 in which the SWCNT 25 is dispersed in the aprotic solvent 23 to the synthetic fiber 10 to attach the conductive ink 24 thereto, and a solvent removal step of drying the synthetic fiber 10 to which the conductive ink 24 is attached to remove the aprotic solvent 23 after the conductive ink impregnation step. According to the method for producing the conductive fiber 1 of the present embodiment, it is possible to provide a method for producing the conductive fiber 1 in which the carbon nanotube conductive film is firmly attached to the synthetic fiber 10.
[0058] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples.
[0059] Example
[0060] (Conductive ink impregnation process)
[0061] The synthetic fibers all use PET fibers made by TEIJIN FRONTIER (Co., Ltd.), namely CALCULO (registered trademark), NANOFRONT (registered trademark), Octa (registered trademark) and WAVERON (registered trademark). All PET fibers are designed to impart sweat-absorbing and quick-drying properties, and are different from conventional PET fibers with circular cross-sections. The cross-sectional shape and fiber diameter of the fibers have the following characteristics. CALCULO has an amorphous cross-sectional shape with deep grooves. NANOFRONT is an ultrafine fiber with a diameter of 700nm and a surface area several dozen times that of ordinary fibers. Octa has an octopus claw-shaped cross-section with eight protrusions arranged radially on an open hollow fiber. WAVERON has a four-peak flat cross-section.
[0062] As raw materials for the conductive ink, eDIPSEC 1.5 (center diameter 1 to 3 nm) manufactured by Najo Nanocarbon Co., Ltd. was prepared as SWCNT and DMF without a dispersant added as an aprotic solvent. Using an ultrasonic homogenizer, SWCNT was dispersed in DMF in such a manner that the content of SWCNT became 0.1% by mass to prepare the conductive ink. The conditions of the ultrasonic homogenizer were a 5-second pulse cycle, an amplitude control of 200 W, and a treatment for 1 hour.
[0063] The conductive ink was impregnated and attached to the PET fibers using a ball mill. The ball mill conditions were set to a speed of 350 rpm and a time of 30 minutes.
[0064] (Solvent Removal Process)
[0065] The PET fibers to which the conductive ink was attached were dried by vacuum drying at about 26° C. for about 6 hours to remove DMF. Then, conductive fibers having a conductive film containing SWCNT formed on the surface of the PET fibers were obtained.
[0066] When CALCULO is used as PET fiber, before the conductive film is formed Figure 4A , the conductive film is formed as Figure 4B , when using NANOFRONT as the PET fiber, before the conductive film is formed Figure 5A , the conductive film is formed as Figure 5B , SEM photographs are shown respectively.
[0067] like Figure 4B As shown, it is possible to confirm that each PET fiber is wound with a state of SWCNT being attached. Since SWCNT is directly wound with the PET fiber, the adhesion of the interface becomes more solid. It is believed that this is because the PET fiber used is a fiber with an amorphous cross-sectional shape with a deep groove on the surface, and also has a random monofilament cross-sectional shape in the axial direction, so the inter-fiber space is large, and it is easy to be wound with SWCNT. In addition, there is a space between the PET fibers, so DMF easily penetrates into the inside of the PET fiber, and the conductive film can be covered on the PET fiber as a whole, and good adhesion can be obtained.
[0068] On the other hand, Figure 5B In the figure, it can be confirmed that the conductive film is tightly stacked in the form of covering the PET fibers in the coagulated state. It is speculated that this is because the PET fibers used are ultrafine fibers with a diameter of 700 nm, and the surface area of the fibers is large, resulting in surface characteristics with high adsorption and gripping properties (high friction), and the adhesion of the interface is improved by the anchoring effect brought about by the fine concavo-convexity on the fiber surface.
[0069] In this way, by utilizing the anchoring effect and contact area expansion effect of the characteristic cross-sectional shape of the PET fiber to improve the adhesion of the interface, the PET fiber and the SWCNT are more easily entangled, and the conductive film can be firmly attached to the PET fiber.
[0070] Fig. 6A This is an optical image showing conductive fibers made using PET fibers (WAVERON, Octa, CALCULO, NANOFRONT). Figure 6B This is an optical image showing a conductive fiber produced in the same manner as above using PET fibers (fiber diameter 50 μm) having a circular cross section that are generally used as a cover for deploying an automobile air bag. Fig. 6A The conductive fibers shown are Figure 6BCompared with the conductive fibers shown, the PET fibers have a smaller fiber diameter and a larger surface area, and therefore it can be seen that the conductive film is uniformly laminated on the entire surface of the PET fibers.
[0071] (evaluate)
[0072] The obtained test samples of the conductive fibers were evaluated by the methods described below.
[0073] <Sheet resistance measurement>
[0074] The sheet resistance of the conductive film of the conductive fiber was measured by the Van der Pauw method. Figure 7 As shown, the magnitude of the current when a current source is connected between the two terminals and the resistances R1 and R2 caused by the potential difference between the two terminals on the other side are obtained, and the correction coefficient f determined by the ratio of the resistances R1 and R2 (R1>R2) is obtained using a numerical table. Then, the sheet resistance Rs (Ω) is calculated by solving the following mathematical formula (2).
[0075] Rs=(π / ln2)·(R1+R2) / 2·f(R1 / R2) (2)
[0076] [Table 1]
[0077] CALCULO NANOFRONT Octa WAVERON Sheet resistance (Ω / sq.) 10.8 31.4 27.9 38.6
[0078] The results of sheet resistance measurements (average value of n=5) for conductive fibers produced by using PET fibers (CALCULO, NANOFRONT, Octa, WAVERON) and impregnating the fibers with conductive ink using a ball mill are shown in Table 1. It can be seen that the lowest value of 10.8Ω / sq. is shown when CALCULO is used in PET fibers, indicating good conductivity. It should be noted that the sheet resistance when CALCULO is used in PET fibers is 10.8Ω / sq. for the first time, 11.8Ω / sq. for the second time, 8.4Ω / sq. for the third time, 11.7Ω / sq. for the fourth time, and 5.2Ω / sq. for the fifth time, with small deviations for each sample and stable values. This is believed to be because, for example, Figure 4B As shown, SWCNTs are entangled and attached to each PET fiber, so the electrical conductivity of the surface is good and stable characteristics can be obtained.
[0079] <Electromagnetic wave shielding properties>
[0080] The electromagnetic wave shielding properties of the conductive fibers were evaluated. Figure 8As shown, a vector network analyzer (VNA) 60 and a waveguide 63 are connected by a coaxial cable 61, and a conductive fiber is inserted as a shielding material 62 between the waveguides 63 to measure the shielding effect (SE). The shielding effect SE (dB) can be calculated according to the following formula (3), which is obtained from the intensity ratio of the input wave E1 from port 1 and the output wave E4 from port 2.
[0081] SE = 20·log 10 (E4 / E1) (3)
[0082] The sheet resistance and shielding effect SE of the conductive fiber produced by repeatedly impregnating the conductive ink using a ball mill four times using PET fiber (CALCULO) were measured.
[0083] The sheet resistance of the product impregnated four times was 2.6Ω / sq. As shown in Table 1, the sheet resistance of the conductive fiber (CALCULO) produced by impregnation with the conductive ink once was 10.8Ω / sq., whereas the sheet resistance of the product impregnated four times was further reduced.
[0084] On the other hand, the electromagnetic wave shielding property of the 4-time impregnation product was measured, and the shielding effect SE was -33dB. Generally, the shielding effect SE is recommended to be below -20dB, so a good shielding effect was obtained in the 4-time impregnation product. Figure 4B As shown, SWCNTs are entangled and attached to each PET fiber of the conductive fiber. It is believed that by performing the four times of impregnation with the conductive ink, the amount of SWCNTs attached to the PET fiber is further increased, the surface conductivity is further improved, and a conductive fiber with a stable electromagnetic wave shielding effect can be obtained.
[0085] Several embodiments of the present invention have been described above, but these embodiments are presented as examples and are not intended to limit the scope of the invention. These new embodiments can be implemented in various other ways, and various omissions, substitutions, and changes can be made without departing from the scope of the subject matter of the invention. These embodiments and their variations are included in the scope and subject matter of the invention, and are included in the invention recorded in the claims and the scope of their equivalents.
Claims
1. A method for producing a conductive fiber, the conductive fiber comprising a synthetic fiber and a conductive film including a single-walled carbon nanotube formed on a surface of the synthetic fiber, The manufacturing method has the following features: a conductive ink impregnation step of impregnating the synthetic fibers with conductive ink in which the single-walled carbon nanotubes are dispersed in an aprotic solvent to cause the synthetic fibers to adhere thereto; and The solvent removal step is to dry the synthetic fiber to which the conductive ink is attached after the conductive ink immersion step to remove the aprotic solvent.
2. The method for producing a conductive fiber according to claim 1, wherein: The synthetic fiber is polyester fiber.
3. The method for producing a conductive fiber according to claim 1 or 2, wherein: The aprotic solvent is N,N-dimethylformamide.
4. The method for producing a conductive fiber according to claim 1 or 2, wherein: Prior to the conductive ink impregnation step, a pretreatment step of impregnating the synthetic fiber in polydopamine is provided.
5. The method for producing a conductive fiber according to claim 1 or 2, wherein: The temperature in the solvent removal step is equal to or lower than the glass transition temperature of the synthetic fiber.
6. The method for producing conductive fiber according to claim 5, wherein: The solvent removal step uses a vacuum drying method.
7. The method for producing a conductive fiber according to claim 1 or 2, wherein: A ball mill is used in the conductive ink impregnation step.
8. The method for producing a conductive fiber according to claim 1 or 2, wherein: The conductive ink does not contain a surfactant.
Citation Information
Patent Citations
Electroconductive fibers with carbon nanotubes deposited thereon, electroconductive threads, fiber structure, and process for producing same
JP2010059561A